Tantangan Penggunaan E Commerce Bagi Franchise D’top Di Kota Sukabumi Sebagai Strategi Bertahan - Iksan Setiandi, Muhammad; Destian Pratama, Rizky; Ali Maulana, Resta; Gusti Rahayu, Ripaldi (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2025)
Franchise, as one of the most popular business models, is facing new challenges with the rise of e-commerce. This study aims to identify the challenges faced by D’Top franchise businesses in Sukabumi in utilizing e-commerce as a survival strategy. This research used a descriptive qualitative approach with subjects consisting of actively operating D’Top franchisees. Data were collected through semi-structured interviews and analyzed thematically. The results indicate three main challenges: limited human resources, low digital literacy, and lack of support from the franchisor. Despite these issues, several franchisees have taken independent initiatives to adapt digitally through social media and delivery platforms. These findings highlight the importance of franchisor support and external assistance in facilitating the digitalization process in franchise businesses. This study provides a real picture of local franchise practices and contributes to the development of adaptive, technology-based strategies in the franchise sector.